2016
DOI: 10.1111/jdv.13579
|View full text |Cite
|
Sign up to set email alerts
|

The role of topical dermocosmetics in acne vulgaris

Abstract: Acne is a common chronic inflammatory disease and treatment modalities based on acne severity are well established. The role of dermocosmetics in dermatology, and in particular acne, is becoming more important as more research elucidates the mechanisms of action of products in the pathogenesis of acne. Dermocosmetics have the potential to be used as monotherapy or in combination with medical treatment. Therefore, it has become important for dermatologists to understand dermocosmetics to effectively and appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
117
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 59 publications
(116 reference statements)
1
117
1
6
Order By: Relevance
“…However, the safety and efficacy profiles of all these therapies is often considered as problematic, and several studies demonstrated that these treatments are not capable of affecting all etiological factors involved in acne pathogenesis . Therefore, there is an urgent need to further develop alternative and innovative treatments, such as light, laser, and photodynamic therapies (PDT) . Light and laser therapy for the treatment of acne vulgaris is based on the observation that P. acnes synthesizes chromophores such as porphyrins, more specifically, coproporphyrin .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the safety and efficacy profiles of all these therapies is often considered as problematic, and several studies demonstrated that these treatments are not capable of affecting all etiological factors involved in acne pathogenesis . Therefore, there is an urgent need to further develop alternative and innovative treatments, such as light, laser, and photodynamic therapies (PDT) . Light and laser therapy for the treatment of acne vulgaris is based on the observation that P. acnes synthesizes chromophores such as porphyrins, more specifically, coproporphyrin .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Therefore, there is an urgent need to further develop alternative and innovative treatments, such as light, laser, and photodynamic therapies (PDT). [6][7][8][9] Light and laser therapy for the treatment of acne vulgaris is based on the observation that P. acnes synthesizes chromophores such as porphyrins, more specifically, coproporphyrin. [10][11][12] Porphyrins enable light therapy to exert a selective cytotoxic effect on P. acnes.…”
Section: Introductionmentioning
confidence: 99%
“…Cosmetics for oily skin should have multi-directional effects, such as: sebostatic (inhibition of excessive amounts of sebum), bacteriostatic (limiting the growth of bacteria Propionibacterium acnes), inhibition of the oxidation of lipids, soothing irritations (skin irritation increases seborrhoea), keratolytic action, and a mattifying effect (absorbing sebum from the surface) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin B3 is used in the treatment of various skin diseases because it regulates moisture, exfoliates the skin, and eliminates inflammation. Niacinamide reduces the excessive production of sebum and reduces the size of the pores of the skin [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Four main pathways are described in acne pathogenesis: increased sebum production, abnormal keratinization, Propionibacterium acnes colonization, and inlammation [2]. Acne is a multifactorial disease and sometimes associated with systemic disorders.…”
Section: Introductionmentioning
confidence: 99%